Simultaneous determination of nine phenolic compounds in imitation wild Dendrobium officinale samples using ultrahigh-performance liquid chromatography–tandem mass spectrometry - Mu, Yingsu; Cheng, Li; Gong, Xiaojian; Ma, Jiangxiong; Zhang, Shiyu; Mu, Yinghua; Liang, Kang; Zhou, Xin; Zhao, Chao (Frontiers in Nutrition, 2023)
Dendrobium officinale Kimura et Migo (D. officinale), one of the nine everlasting types of grass, has gained increasing attention owing to its important roles in alternative medicines and drug discovery. Due to its natural resources being in danger of being extinct, imitation wild planting is becoming increasingly common. To assess the product's quality completely, an efficient ultrahigh performance liquid chromatography-triple quadrupole tandem mass spectrometry (UHPLC-QQQ-MS/MS) method was established to simultaneously quantify nine phenolic compounds in D. officinale samples. The extraction parameters, including solvent, solvent concentration, solid‒liquid ratio, and extraction time, were systematically optimized with the single-factor test. The results demonstrated that extraction with a 1:200 solid-to-liquid ratio of 80% methanol for 1.5 h was the most efficient condition for the extraction of flavonoids. Satisfactory retention times and resolution of the nine analytes were acquired on the Thermo Scientific Hypersil GOLD column with MRM in negative ion scanning mode. The method was validated to demonstrate its selectivity, linearity, precision, accuracy, and robustness. Thus, the verified UHPLC-QQQ-MS/MS method was successfully applied to the quantification of phenolic components present in D. officinale samples. The results indicated that the quantity and composition of phenolic components in D. officinale from various provenances were significantly different. This work provides a theoretical foundation for the cultivation and assessment of wild D. officinale quality.